Evaluation of the benefits of stem cell therapy in healing Anterior Cruciate Ligament (ACL) injuries - Khu, Adrian (Universitas Aisyah Pringsewu, 2023)
PONV (Post Operative Nausea and Vomiting) or post-operative nausea and vomiting is a side effect that is often found after surgery and anesthesia. For patients, PONV is felt to be very disturbing, so PONV is called the big little problem. Factors related to PONV are patient factors, anesthesia factors, and surgical factors. Regarding surgical factors, the type of surgery that is at high risk for PONV is orthopedic surgery (22%). In addition, the relatively long duration of surgery and excessive surgical manipulation can also cause PONV in orthopedic surgery. To identify risk factors for PONV, a calculation for PONV has been developed. Based on research from (Donnerer, 2003), data from Koivuranta et al was combined with Apfel et al in developing this PONV risk score. The PONV risk score indicates that there are 4 (four) initial factors in determining PONV risk factors, namely female gender, history of PONV or motion sickness, history of not smoking, and history of using postoperative opioids to treat pain. Not only PONV risk factor scores for adult patients, there are also PONV risk factor scores for pediatric patients or Postoperative Vomiting in Children score. POVOC score is simplified as follows with the risk factor of duration of surgery 30 minutes, age 3 years, strabismus surgery, and positive history of PONV or motion sickness from parents or siblings. In preventing the occurrence of PONV, two approaches can be taken, namely a pharmacological approach and a non-pharmacological approach. The pharmacological approaches used are ondansetron and metoclopramide. Ondansetron is a 5-HT3 receptor antagonist. Whereas Metoclopramide inhibits dopamine (D2) receptors centrally and peripherally. This study aims to examine studies on the use of antiemetic drugs in preventing postoperative nausea and vomiting in orthopedic surgery patients at Rumkital in April 2023. The research was conducted in a cross-sectional-prospective manner and has been declared